Genetic regulation of expression of leukotriene A4 hydrolase. Issue 1 (9th February 2016) - Szul, Tomasz; Castaldi, Peter; Cho, Michael H.; Blalock, J. Edwin; Gaggar, Amit
In chronic inflammatory lung disorders such as chronic obstructive pulmonary disease (COPD), the concurrent organ-specific and systemic inflammatory responses lead to airway remodelling and vascular dysfunction. Although a major common risk factor for COPD, cigarette smoke alone cannot explain the progression of this disease; there is increasing evidence that genetic predisposition also plays a role in COPD susceptibility and progression. A key enzyme in chronic lung inflammation is leukotriene A4 hydrolase (LTA4H). With its aminopeptidase activity, LTA4H degrades the neutrophil chemoattractant tripeptide PGP. In this study, we used the luciferase reporter gene analysis system and quantitative trait locus analysis to explore the impact of single-nucleotide polymorphisms (SNPs) in the putative promoter region of LTA4H on LTA4H expression. We show that not only is the putative promoter of LTA4H larger than previously reported but also that SNPs in the expanded promoter region regulate expression of LTA4H both in cell-based systems and in peripheral blood samples from human subjects. These findings provide significant evidence for an active region upstream of the previously reported LTA4H promoter, which may have implications related to ongoing inflammatory processes in chronic lung disease. SNPs in the putative promoter region of LTA4H specifically affect the expression of leukotriene A4 hydrolase http://ow.ly/VCSNE